Three-Dimensional Bi2Fe4O9 Nanocubes Loaded on Reduced Graphene Oxide for Enhanced Electromagnetic Absorbing Properties - Lu, Min; Sun, Yuan-Kai; Yang, Shu-Hao; Wang, Hui-Ya; Guan, Xiao-Hui; Wang, Guang-Sheng (Frontiers in Chemistry, 2020)
Bi2Fe4O9(BFO) nanocubes were prepared in proportion using a simple and easy hydrothermal method, and were then assembled on reduced graphene oxide (rGO) multilayered sheets. The excellent microwave absorption properties of Bi2Fe4O9/rGO nanohybrids were achieved by properly adjusting the impedance matching and getting a high attenuation capability contributed from different ratios of the BFO and rGO. A minimum reflection loss value of −61.5 dB at 12.8 GHz was obtained with a Bi2Fe4O9/rGO ratio of 2:1, and the broadest bandwidth below −10 dB was up to 5.0 GHz (from 10.8 to 15.8 GHz) with a thickness of 2.4 mm. Additionally, the elementary mechanism of wave absorption performance is also investigated.